Impact of Environmental Protection Regulations on Corporate Performance From Porter Hypothesis Perspective: A Study Based on Publicly Listed Manufacturing Firms Data - Mu, Shaohong; Wang, Xianglu; Mohiuddin, Muhammad (Frontiers in Environmental Science, 2022)
Environmental protection regulations contribute to cleaner production and enhance performance of manufacturing firms. We take China's new "Environmental Protection Regulations (2015), as a qua-si-natural experiment, using A-share listed companies in Shenzhen and Shanghai in 2012–2017 as a research sample. Using the propensity score matching and double difference (PSM-DID) method, we empirically test the impact of environmental regulations on the financial performance of these companies. The results show that the new Environmental Protection Law has significantly improved corporate profits of large firms. But does not significantly increase investment on R&D and innovation. "Compliance cost heterogeneity" caused by the size difference of firms can better explain the impact of environmental regulations on the profit margin of listed manufacturing firms. The results show how firms can improve their performance by developing environment friendly production systems.